Awareness of medical radiation exposure among patients: A patient survey as a first step for effective communication of ionizing radiation risks. (November 2017) - Ria, F.; Bergantin, A.; Vai, A.; Bonfanti, P.; Martinotti, A.S.; Redaelli, I.; Invernizzi, M.; Pedrinelli, G.; Bernini, G.; Papa, S.; Samei, E.
Highlights: 2013/59/EURATOM requires patient radiation dose to be included in radiological report. There is the need to know the actual patient's knowledge level. Patients agree that it is important to know the radiological radiation level. There is little awareness in terms radiation level related to medical exposure. Medical physicists and radiologists can convey correct and effective information. Abstract: Introduction: The European Directive 2013/59/EURATOM requires patient radiation dose information to be included in the medical report of radiological procedures. To provide effective communication to the patient, it is necessary to first assess the patient's level of knowledge regarding medical exposure. The goal of this work is to survey patients' current knowledge level of both medical exposure to ionizing radiation and professional disciplines and communication means used by patients to garner information. Material and Methods: A questionnaire was designed comprised of thirteen questions: 737 patients participated in the survey. The data were analysed based on population age, education, and number of radiological procedures received in the three years prior to survey. Results: A majority of respondents (56.4%) did not know which modality uses ionizing radiation. 74.7% had never discussed with healthcare professionals the risk concerning their medical radiological procedures. 70.1% were not aware of the professionals that have expertise to discuss the use of ionizing radiation for medical purposes, and 84.7% believe it is important to have the radiation dose information stated in the medical report. Conclusion: Patients agree with new regulations that it is important to know the radiation level related to the medical exposure, but there is little awareness in terms of which modalities use X-Rays and the professionals and channels that can help them to better understand the exposure information. To plan effective communication, it is essential to devise methods and adequate resources for key professionals (medical physicists, radiologists, referring physicians) to convey correct and effective information.